Effect of vegetation structure on above ground biomass in tropical deciduous forests of Central India. Issue 21 (2nd November 2022) - Lal, Preet; Kumar, Amit; Saikia, Purabi; Das, Anup; Patnaik, C.; Kumar, Gajendra; Pandey, A. C.; Srivastava, Parul; Dwivedi, C. S; Khan, M. L.
Abstract: The study aimed to determine the above-ground biomass (AGB) of tropical deciduous forests in Central India using field-based techniques and spaceborne quad-pol ALOS PALSAR-2 L-band and dual-pol Sentinel 1A C-band synthetic aperture radar (SAR). Field sampling based on 73 forested grids exhibited a diverse forest composition in the Satpura Tiger Reserve (STR) with a total of 54 tree species of which 31.48% species were IUCN Red-Listed. The forests were highly diverse ( H ′=3.22) with a low concentration of dominance (CD = 0.06) and a quite high species evenness ( E = 0.81). The sensitivity and correlation between field-based AGB and SAR backscatter in STR were highest in cross-polarization due to its higher sensitivity to the vegetation structure in both L- and C-band SAR, where L-VH based AGB estimates were found more accurate (RMSE:5.17%). The study provided vital information for setting up strategies for biodiversity conservation, enhancing forest productivity, and restoring wildlife habitats.